Enhancing students’ motivation to learn software engineering programming techniques: a collaborative and social interaction approach - Nunes, Ricardo Rodrigues (2015)
To motivate students to study advanced programming techniques, including the use of architectural styles such as the model–view–controller pattern, we have con-ducted action research upon a project based-learning approach. In addition to collabo-ration, the approach includes students’ searching and analysis of scientific documents and their involvement in communities of practice outside academia. In this paper, we report the findings of second action research cycle, which took place throughout the fourth semester of a six-semester program. As with the previous cycle during the pre-vious academic year, students did not satisfactorily achieve expected learning out-comes. More groups completed the assigned activities, but results continue to reflect poor engagement in the communities of practice and very low performance in other learning tasks. From the collected data we have identified new approaches and recom-mendations for subsequent research.